2009
DOI: 10.14723/tmrsj.34.237
|View full text |Cite
|
Sign up to set email alerts
|

Oxide-ion conduction and dielectric relaxations in Ca-stabilized ZrO<sub>2</sub>

Abstract: The dielectric properties of Ca-stabilized ZrO 2 (Zr 0.9 Ca 0.1 O 2-δ , 10CSZ) which is an oxide ion conductor were investigated. Numerical analyses for the frequency dependence of dielectric constant (ε r ′) and dielectric loss factors (ε r ″) revealed that the dielectric properties were made up of Debye-type polarization due to dopant-vacancy associates [Ca zr ″-V o¨] and interfacial polarization at electrolyte-electrode. Two Debye-type relaxations were observed. This result implies the existence of two dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It is anticipated that the YZrVO.. distance in the Non‐LTD 1700 ceramics will be greater than that in the Non‐LTD 1500 sample, which is related to the fact that the higher sintering temperature allows for larger translational movements of oxygen vacancies. Oxygen associates with the different distance between CaZr and VO.. have been reported in Ca‐doped ZrO 2 ceramics 43 . Therefore, the higher dielectric permittivity and loss of the Non‐LTD 1700 ceramics can be attributed to a possible long distance between YZr and VO..in the oxygen vacancy associated (YZrVO..) dipoles.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…It is anticipated that the YZrVO.. distance in the Non‐LTD 1700 ceramics will be greater than that in the Non‐LTD 1500 sample, which is related to the fact that the higher sintering temperature allows for larger translational movements of oxygen vacancies. Oxygen associates with the different distance between CaZr and VO.. have been reported in Ca‐doped ZrO 2 ceramics 43 . Therefore, the higher dielectric permittivity and loss of the Non‐LTD 1700 ceramics can be attributed to a possible long distance between YZr and VO..in the oxygen vacancy associated (YZrVO..) dipoles.…”
Section: Resultsmentioning
confidence: 86%
“…For Y (8 and 9 mol%) doped ZrO 2 , it was reported that these defect dipole pairs are responsible for the dielectric relaxation at radio frequencies. 22,43 There is 2.1% and 7.7% of the monoclinic M phase in the Non-LTD 1500 and Non-LTD 1700 samples. The lower percentage of the M phase, the higher concentration of the oxygen vacancy related associates.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Our research group reported that the relationship between oxide ion conduction and dielectric relaxation from the viewpoints of dielectric constant, dielectric loss factor and loss tangent (tanδ) in the Sm, Nd, or Yb doped CeO 2 [4][5][6] and Y or Ca stabilized ZrO 2 [7,8] systems. According to those studies, the dielectric properties of oxide ion conductors can be explained by the superposition of Debye-type polarization due to the dopant-vacancy associates [Ln Ce ′-V O¨] ‧ (Ln: dopant cation) and charge current on electrolyte-electrode interface.…”
Section: Introductionmentioning
confidence: 99%